Violation of the Conversational Maxims in the Humorous Utterances in Comedy Program ‘The East’ - Angelina Kencana (Institute of Research and Community Outreach - Petra Christian University, 2021)
This study is conducted in order to reveal the violated maxims in the humorous utterances and the implicature of the maxim violations in NET comedy program ‘The East’, from a discourse analysis point of view. The writer analyzes the types of maxims that are violated found in the humorous utterances in episode 397 entitled ‘Ribet Milih Tempat Kerja Baru’ (Complication in choosing a workplace) of the comedy program ‘The East’. This study is conducted by using a descriptive-qualitative approach, aimed to create a description from the perspectives or experiences of the writer. The findings reveal there are totally 26 (twenty-six) violations, each with its implied meaning in the episode of the program. Among the four maxims, the most frequent occurrence is the violation of maxim of Quality with 11 occurrences. Key words: Cooperative Principle, violation of conversational maxims, implicature